Teacher Education In and For Uncertain Times (Springer Singapore, 2018)
This volume considers the role of initial and continuing teacher education in uncertain times. It highlights key principles and methods that preserve curiosity and optimism regarding the potential of teacher education, and regarding the manifold achievements of pre-service and in-service teachers. It explores how teacher education can produce teachers who are committed to counter-oppressive curricula and pedagogies, and reflects the critical role of teacher educators as public academics.